Curricular Landscapes: Preservice Teachers’ Perceptions of Place and Identity - Courtland, Mary Clare; Hammett, Roberta; Strong-Wilson, Teresa; Bainbridge, Joyce; Johnston, Ingrid; Burke, Anne; Ward, Angela; Wiltse, Lynne; Gonzales, Ismel; Shariff, Farha (Journal of the Canadian Association for Curriculum Studies, 2009)
The longitudinal study explored preservice teachers’ understandings of Canadian identity and representations of identity in Canadian multicultural picture books. The design involved descriptive case studies in six Faculties of Education across six provinces. Some participants viewed place as related to landscape and geography; some perceived place as a site for promoting sociocultural understanding; others articulated critical discourse of place. Perspectives ranged from sophisticated understandings of Canadian identity and representations in the picture books to resistance to representations or issues that disrupt a dominant (white) perspective of a benevolent multicultural Canada.